Penguatan Kompetensi Tenaga Administrasi Sekolah melalui Pelatihan Kerja Berbasis Dapodik - Jahani; Junaina (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Digital transformation in school governance requires administrative staff to possess adequate competence in managing educational data accurately, timely, and accountably through the Basic Education Data System (Dapodik). This study aims to analyze the strengthening of school administrative staff competence through Dapodik-based on-the-job training and to identify changes in competence, supporting factors, and inhibiting factors in its implementation. This study employed a qualitative approach with a school-based case study design at SMA Negeri 5 Pontianak. Data were collected through training documentation, observation of administrative work practices, comparison of conditions before and after mentoring, and reflective notes on the training process. The data were analyzed descriptively and qualitatively by categorizing findings based on initial competence conditions, training implementation, competence changes, and supporting and inhibiting factors. The findings show that Dapodik-based on-the-job training conducted through direct practice, demonstration, guided trials, supervision, and follow-up strengthened administrative staff independence in operating Dapodik, using information technology, entering student and teacher data, understanding validation and synchronization procedures, and improving confidence in delivering digital administrative services. The main supporting factors included principal support, mentoring by the head of school administration, collaboration among teachers and students in providing data, and the availability of technological facilities, while the inhibiting factors included infrastructure limitations and the risk of unproductive internet use. This study concludes that Dapodik is not only a national education data platform but can also serve as a contextual medium for human resource competence development through work-based training. The implication of this study highlights the importance of continuous mentoring, digital administrative supervision, adequate technological support, and periodic competence evaluation as part of strengthening data-based school governance.